Audit Committees and its effect on Environmental, Social, and Governance Disclosure - Grave, M.; Paiva, I. (17th Iberian Conference on Information Systems and Technologies (CISTI), 2022)
This paper analyzes the link between independent board members on audit committees (AC) and specific information attributes of environmental, social, and governance (ESG) disclosures. Our results reveal a positive association of the audit committees and the quality of voluntary ESG reporting, which results in greater comprehensiveness and relevance. These findings extend the academic debate concerning the role of independent directors on sustainability policies. Moreover, given the importance of ESG information in capital markets and its potential benefits for firms, this evidence may help regulators and owners to implement adequate corporate governance mechanisms.